Effects of surfactant on corrosion behavior of carbon steel in simulated eor crude oil - Zakaria, Mohammad; Suryanto, -; Hilmy, Irfan (2014)
Enhanced Oil Recovery (EOR) is a technique used in oil and gas industries to increase the amount of crude oil production by injection of brine, a mixture of surfactant, water and seawater. As the results, crude oil contains brine which is corrosive. Surfactant is used to lessen the corrosion effect in addition to increase flowing of oil. In this study, the effect of surfactant on corrosion behavior of carbon steel in simulated enhanced oil recovery crude was investigated. Autoclave machine was used to perform corrosion experiment in the oxygen free environments. Corrosion rate was measure using weight loss method. The results show that surfactant reduces corrosion rate of carbon steel from 0.061 mm/y to 0.042 mm/y and the corrosion type on carbon steel was uniform corrosion.